Indonesia - Rush, Jason (Impact stories, 2008)
Over the last 4 decades, the Asian Development Bank (ADB) has been helping the Government of Indonesia achieve its vision of a country free of poverty. In this publication, we tell the stories of the people and places this partnership has helped.